Hydrogen isotopic composition of the Martian mantle inferred from the newest Martian meteorite fall, Tissint. (6th September 2016) - Mane, P.; Hervig, R.; Wadhwa, M.; Garvie, L. A. J.; Balta, J. B.; McSween, H. Y.
Abstract: The hydrogen isotopic composition of planetary reservoirs can provide key constraints on the origin and history of water on planets. The sources of water and the hydrological evolution of Mars may be inferred from the hydrogen isotopic compositions of mineral phases in Martian meteorites, which are currently the only samples of Mars available for Earth‐based laboratory investigations. Previous studies have shown that δD values in minerals in the Martian meteorites span a large range of −250 to +6000‰. The highest hydrogen isotope ratios likely represent a Martian atmospheric component: either interaction with a reservoir in equilibrium with the Martian atmosphere (such as crustal water), or direct incorporation of the Martian atmosphere due to shock processes. The lowest δD values may represent those of the Martian mantle, but it has also been suggested that these values may represent terrestrial contamination in Martian meteorites. Here we report the hydrogen isotopic compositions and water contents of a variety of phases (merrillites, maskelynites, olivines, and an olivine‐hosted melt inclusion) in Tissint, the latest Martian meteorite fall that was minimally exposed to the terrestrial environment. We compared traditional sample preparation techniques with anhydrous sample preparation methods, to evaluate their effects on hydrogen isotopes, and find that for severely shocked meteorites like Tissint, the traditional sample preparation techniques increase water content and alter the D/H ratios toward more terrestrial‐like values. In the anhydrously prepared Tissint sample, we see a large range of δD values, most likely resulting from a combination of processes including magmatic degassing, secondary alteration by crustal fluids, shock‐related fractionation, and implantation of Martian atmosphere. Based on these data, our best estimate of the δD value for the Martian depleted mantle is −116 ± 94‰, which is the lowest value measured in a phase in the anhydrously prepared section of Tissint. This value is similar to that of the terrestrial upper mantle, suggesting that water on Mars and Earth was derived from similar sources. The water contents of phases in Tissint are highly variable, and have been affected by secondary processes. Considering the H2 O abundances reported here in the driest phases (most likely representing primary igneous compositions) and appropriate partition coefficients, we estimate the H2 O content of the Tissint parent magma to be ≤0.2 wt%.